The Use of Multidimensional Nomial Logistic Model and Structural Equation Model in the Validation of the 14-Item Health-Literacy Scale in Chinese Patients Living with Type 2 Diabetes - Wu J; Tao Z; Gao N; Shen J; Chen ZL; Zhou H; Zheng S (Dove Medical Press, 2023)
JianBo Wu,1,* ZhuJun Tao,1,* NingZhou Gao,1 Jie Shen,1 Zhi-Long Chen,1 HaiFeng Zhou,1 SongBai Zheng2 1Department of Pharmacy, Huadong Hospital, Fudan University, Shanghai, People's Republic of China; 2Department of Geriatrics, Huadong Hospital, Fudan University, Shanghai, People's Republic of China*These authors contributed equally to this workCorrespondence: HaiFeng Zhou, Department of Pharmacy, Huadong Hospital, Fudan University, Shanghai, People's Republic of China, Tel +86 13918194105, Email zhouhaifeng23@126.comObjective: To evaluate the psychometric properties of the 14-item health literacy scale (HL-14) in patients living with type 2 diabetes mellitus (T2DM) in clinical setting.Methods: Cross-sectional study using item response theory and structural equation modeling (SEM) for testing the item difficulty and three dimensional-HL configurations was adopted in this study. Chinese patients living with T2DM admitted to endocrinology department of Huadong hospital were evaluated by the HL-14 including communication, functional and critical health literacy from August to December 2021.Results: The multidimensional random coefficients multinomial logistic model indicated the difficulty settings of the scale are appropriate for the study populations, and differential item functioning was not observed for sex in the study. SEM demonstrated that the three-dimensional configuration of the scale is good in the study population (x2/df=2.698, Comparative Fit Index = 0.965, Root Mean Square Error of Approximation = 0.076, standard residual mean root = 0.042).Conclusion: The HL-14 scale is a reliable and valid measurement, which can perform equitably across sex in evaluating the health literacy in Chinese patients living with T2DM. Moreover, the scale may help fill the gaps of multidimensional health literacy assessment and rapid screening of health literacy ability for clinical practice.Keywords: health literacy, type 2 diabetes, psychometric properties, multidimensional item response theory, structural equation model